If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -36x + -450 = -135 Reorder the terms: -450 + x + -36x = -135 Combine like terms: x + -36x = -35x -450 + -35x = -135 Solving -450 + -35x = -135 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '450' to each side of the equation. -450 + 450 + -35x = -135 + 450 Combine like terms: -450 + 450 = 0 0 + -35x = -135 + 450 -35x = -135 + 450 Combine like terms: -135 + 450 = 315 -35x = 315 Divide each side by '-35'. x = -9 Simplifying x = -9
| 3x+5=2-2x | | 3x-9+5=2-2x | | 8820=(n-2)*180 | | 8100=(n-2)*180 | | 11u+9-4u+33= | | (25-x^2)^(1/2) | | 12y-3x=7 | | 6y+2(2y+3)=6 | | (3y+9)2=81 | | 3060=(n-2)*180 | | v^-2*v/v^-1 | | S=-d+71 | | 16r-19+5r+24= | | (N-2)*180=8100 | | x-38.25=24.45 | | 1/4x(3x7) | | (N-2)*180=6480 | | 14w+56=7(w+2)-14 | | (N-2)*180=3780 | | 14w+8=7(w+2)-14 | | F(x)=13-1/3x | | 2517636.50+615493x=(3*648043)+648043x | | (N-2)*180=3060 | | 2517636.50+615493=(3*648043)+648043x | | 7r+4(1+r)= | | c=(3.14)(42) | | 1+4x=-3 | | -16t^2+112t+128=192 | | ((4/5)*((-15)-7 | | x(x+6)=192 | | 4x-6+7x=3x+6 | | -16t^2+96t+112=192 |